2008
DOI: 10.1007/s11274-008-9710-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of phosphate and potash rocks with Acidithiobacillus on sugarcane yield and their effects on soil chemical attributes

Abstract: Experiments were conducted to evaluate the effectiveness of biofertilizers produced from phosphate and potash rocks mixed with sulfur inoculated with Acidithiobacillus oxidizing bacteria on sugarcane yield and their effects on some chemical attributes of a Brazilian tableland soil. The experiment was arranged in a completely randomized factorial design 2 9 4 9 3 + 1, with four replicates. Two varieties of sugarcane, four rates of three sources of P and K (apatite + biotite, P + K biofertilizers with Acidithiob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
(9 reference statements)
2
24
0
Order By: Relevance
“…After inoculation, the trays were incubated for 30 days at 28 ±5 °C. The humidity was maintained near the water holding capacity using distilled water, according to Stamford et al (2008). Samples were collected, and the total N content was determined by the Kjeldhal method, using the Kjeltec auto analyzer (1030 Model).…”
Section: Production Of Biofertilizer With Free Living Diazotrophic Bamentioning
confidence: 99%
See 4 more Smart Citations
“…After inoculation, the trays were incubated for 30 days at 28 ±5 °C. The humidity was maintained near the water holding capacity using distilled water, according to Stamford et al (2008). Samples were collected, and the total N content was determined by the Kjeldhal method, using the Kjeltec auto analyzer (1030 Model).…”
Section: Production Of Biofertilizer With Free Living Diazotrophic Bamentioning
confidence: 99%
“…Several studies conducted on acidic soil from rainforest regions have shown that plant yield is reduced as a function of acidity. These studies indicated that it is controlling this specific problem will improve the productivity and quality of crops (Stamford et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations